Fabrication of Fully Printable Flexible Large Area Microsupercapacitors - da Silva, Romário Justino; Fernandes, Silvia Leticia [UNESP]; de Souza Miranda, Barbara Hellen; Amorin, Gabriela; de Queiroz Vilaça, Rodrigo; Bagnis, Diego; de Melo, Celso Pinto (Wiley, 2025)
ABSTRACT We produced microsupercapacitors (MSCs) using a PEDOT:PSS/CNT ink on both rigid (glass/ITO) and flexible (PET/IMI) substrates via doctor blade coating and laser scribing. The highest capacitance of 24.8 mF cm −2 was obtained for glass/ITO substrates with 60 μm electrode spacing, with a recorded equivalent series resistance (ESR) of 30.6 Ω. Flexible PET/IMI devices exhibited lower capacitance (21.2 mF m −2 ) and approximately twice the ESR of their rigid counterparts, highlighting the impact of substrate choice on electrochemical performance. The proposed fabrication methodology enables the scalable production of high‐quality MSCs with excellent electrochemical stability, retaining 80% of their initial capacitance after 5000 charge–discharge cycles and exhibiting a low leakage current (~40 μA). The combination of pseudocapacitance and EDLC mechanisms contributes to efficient charge storage in compact, flexible, and planar architectures. These results demonstrate the feasibility of integrating MSCs into emerging energy storage applications, including flexible electronics, IoT, and wearable devices.